Measuring the Price of Housing Consumption for Owners in the CPI - Timothy K.M. Beatty; Erling Røed Larsen; Dag Einar Sommervoll (Statistics Norway, Research Department, 2005)
Measuring change in the price of housing is an important and notoriously difficult task for national statistical agencies. Different approaches have been attempted, but suffer from known weaknesses. This article suggests dividing housing outlays into consumption and saving. The changes in prices of the consumption component are governed primarily by the purchasing price and the interest rate, and lead us to the construction of a consumption cost index. We show that over the lifespan of the mortgage, under some general assumptions, the price changes most relevant for inflation measurement can be obtained from a housing price index. The main challenge lies in computing weights for the housing consumption index. We demonstrate how this can be done in practice. An empirical example using data from Norway shows that over the 12-month period from June 2003 to June 2004 the official inflation was measured at 1.3%. This did not properly account for a 10.2% increase in house prices. The methodology proposed in this paper estimates the 12-month inflation at 3.4%.
Keywords: D1; E3; E5; 330; asset price inflation; consumer price index; consumption cost; housing prices; inflation measurement; mortgage; rental equivalence; user cost